2009
DOI: 10.1007/s10800-009-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of hydroxyethyl imidazoline as H2S corrosion inhibitor using electrochemical noise and electrochemical impedance spectroscopy

Abstract: A study of H 2 S corrosion inhibition of pipeline steel by hydroxyethyl imidazoline has been carried out by using electrochemical techniques. Inhibitor concentration included 5, 10, 25, 50, and 100 ppm in a H 2 S-containing 3% NaCl solution at 50°C. Techniques included linear polarization resistance (LPR), electrochemical impedance spectroscopy (EIS), and electrochemical noise (EN) measurements. In addition to the traditional noise in voltage and current, noise resistance (R n ) measurements were used. All tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…An inhibitor concentration of 50 ppm was found to afford a corrosion inhibition efficiency of 98%. In a similar investigation by Lucio-Garcia et al [116], 5 and 10 ppm hydroxyethyl imidazoline were found to protect API X120 steel by almost 95% at 50 C. Although these authors claimed the modified imidazoline compounds were green, it would have been justifiable if experimental results for toxicity, biodegradation, and bioaccumulation tests were provided. In Table 2 is summarized the imidazoline-based inhibitors reported for sour corrosion inhibition of carbon steel.…”
Section: Imidazoline-based Inhibitorsmentioning
confidence: 89%
“…An inhibitor concentration of 50 ppm was found to afford a corrosion inhibition efficiency of 98%. In a similar investigation by Lucio-Garcia et al [116], 5 and 10 ppm hydroxyethyl imidazoline were found to protect API X120 steel by almost 95% at 50 C. Although these authors claimed the modified imidazoline compounds were green, it would have been justifiable if experimental results for toxicity, biodegradation, and bioaccumulation tests were provided. In Table 2 is summarized the imidazoline-based inhibitors reported for sour corrosion inhibition of carbon steel.…”
Section: Imidazoline-based Inhibitorsmentioning
confidence: 89%
“…Corrosion inhibitor injection is a standard practice in oil and gas production systems to control internal corrosion in carbon steel structure, Nitrogen-based organic inhibitors, such as imidazolines or their salts have been successfully used in these applications even without an understanding of the inhibition mechanism [5]. Corrosion inhibition of organic compounds is related to the adsorption properties of the organic compounds and depends on the nature and state of the metal surface, type of corrosive environment, and chemical structure of the inhibitor [5].…”
Section: No11 Journal Of Petroleum Research and Studies ( Jpr And S )mentioning
confidence: 99%
“…These oil spillage disasters endangered the natural life and caused an economical loss due to oil or gas loss, out of service time and due to the expenses necessary to deal with oil pollution Carbon steels are generally used for the petroleum industry for transportation of crude oils and gasses from offshore to different refining platforms and from there to different destination of the applications [4]. Mainly there are two types of corrosion in the oil and gas production systems; CO 2 corrosion (sweet corrosion), and H 2 S corrosion (sour corrosion) in the absence of dissolved oxygen [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Corrosion inhibitors can significantly settle this problem, among which, the organic compounds, especially heterocyclic compounds, are the most consumable in oil industry due to their fascinating properties. A large number of heterocyclic compounds are known to be applicable as corrosion inhibitors for steel in H 2 S solution . However, only a few non‐toxic compounds have been investigated as inhibitors.…”
Section: Introductionmentioning
confidence: 99%